HEPATIC GLYCOGENOSIS IN CHILDREN: SPECTRUM OF PRESENTATION AND DIAGNOSTIC MODALITIES - Bilal, Hazrat; Cheema, Huma Arshad; Fayyaz, Zafar; Saeed, Anjum; Hamdani, Syeda Sara Batool (Journal of Ayub Medical College Abbottabad, 2019)
Background: Objectives of the study were to determine the clinical spectrum of presentation and various modalities helpful in the diagnosis of liver glycogenosis short of genetic analysis. Methods: All patients under 18 years of age presenting to Paediatric Gastroenterology unit of Children's Hospital, Lahore with suspicion of hepatic glycogen storage disease (GSD) were enrolled over a period of 18 months. Demographic profile and various factors under observation were recorded. Collected data was analysed using SPSS version 22. Results: Among 89 enrolled patients F:M ratio was (1.28:1). The most common GSD was type I (71, 79.7%) followed by III (13, 14.6%), II (3, 3.3%), IV (1, 1.1%) and IX (1, 1.1%). The Abdominal distension was the most common presentation in 89.5% followed by hepatomegaly in 86.5%, diarrhoea in 41.6%, doll's like appearance in 31.5% and vomiting, acidotic breathing with convulsions in about 20% of children in GSD I. Hepatomegaly (100%), failure to thrive (85%), developmental delay (69%) and splenomegaly (92.3%) were leading presentation in GSD III. Elevated triglycerides (77.5%) followed by transaminesemia (56%), hypercholesterolemia (63%), hyperuricemia (32%) and hypoglycaemia (14%) were significant biochemical findings in GSD I. Consistently raised liver enzymes (92%) and creatinine phosphokinase (100%) in addition to hypertriglyceridemia (69%) were seen in GSD III. The presence of enlarged hepatocytes with clearing of cells favour GSD1 showed in 79% of children while fibrosis and steatosis usually seen in GSD-III (14.6%). Conclusion: Hepatic glycogen storage diseases are serious health issues and should be excluded in any patient who present with hepatomegaly, short stature and hyperlipidaemia to decrease the disease mortality and morbidity. Keywords: glycogen storage disease; children; presentation